Potential Problems Facing the U.S. Nursery Industry - Edward A. Evans (EDIS, 2004)
This fact sheet focuses on the possible impact of free trade on the U.S. nursery industry. The nursery crops covered include ornamental plants and trees with woody stems (broadleaf evergreens, coniferous evergreens, deciduous shade trees, deciduous flowering trees, deciduous shrubs and other ornamentals, fruit and nut plants for home use, cut and to-be-cut Christmas trees, and propagation material or lining-out stock). This is EDIS document FE491, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published August 2004.